JEWS IN EUROPE AND THE BEGINNING OF ARAB-JEWISH CONFLICTS - Lydia Megawati; Hasaruddin Hasaruddin (Universitas Islam Negeri Alauddin Makassar, 2019)
This article discusses the development of Judaism in European and the history of the Arab-Jewish conflict. Researchers in this case uses qualitative methods by collecting library data. The historical approach is an alternative research in tracing the traces of Jews in Europe and the beginning of the Arab-Jewish conflict. The author comes to the conclusion that a change of power, conquest, war has brought the Jewish nation to the pain of continuing suffering. Get discriminatory treatment to be the lowest class and intolerance treatment from the authorities who control the area where they settled. The unfair treatment they received from the authorities until 70 AD when the Jews under Roman rule broke out but ended in failure and caused damage to their own diei. The Temple of Solomon which was the center of their religious worship in Jerusalem was destroyed. These conditions caused the Jewish people to scatter to the outside world which became known as The Great Diaspora.